Growth detection of Cutibacterium acnes from orthopaedic implant-associated infections in anaerobic bottles from BACTEC and BacT/ALERT blood culture systems and comparison with conventional culture media. (February 2020) - Jeverica, Samo; El Sayed, Faten; Čamernik, Petra; Kocjančič, Boštjan; Sluga, Boštjan; Rottman, Martin; Papst, Lea
Abstract: Cutibacterium acnes is a major etiologic agent of orthopaedic implant-associated infections (IAIs) and requires up to 14 days of incubation in an anaerobic atmosphere for growth detection. As blood culture (BC) systems are increasingly being used to monitor the growth of IAI specimens, we compared different BC media for growth detection of C. acnes . Non-duplicate C. acnes isolates (n = 99) obtained from sonicate-fluid cultures of orthopaedic IAIs from Slovenia (n = 54), conventional tissue samples of monomicrobial orthopaedic IAIs from France (n = 43) and two reference strains were inoculated to anaerobic BC bottles of two major BC systems and 3 conventional culture media types (thioglycolate broth, Schaedler and chocolate agar). Growth and time-to-detection (TTD) were recorded. Only Lytic (BACTEC) and SN (BacT/ALERT) bottles consistently detected growth of C. acnes within 14 days with 94% (n = 93) and 92% (n = 91) detection rates, respectively ( p  = 0.79). Lytic was superior to Plus BACTEC medium ( p  < 0.001), while SN was superior to all other BacT/ALERT media ( p  < 0.001). Mean TTD was 128 ± 43 h (61–336 h) for Lytic and 158 ± 65 h (77–336 h) for SN medium. Among the conventional media, 99% (n = 98) of the isolates grew on Schaedler agar, 96% (n = 95) in thioglycolate broth and 74% (n = 73) on chocolate agar. Inconsistent growth of C. acnes in different BC media can critically influence the detection of this major IAI pathogen. Only Lytic (BACTEC) and SN (BacT/ALERT) BC media types were consistently able to detect C. acnes within 14 days of incubation. However, visible growth was observed faster in thioglycolate broth and Schaedler agar media. Highlights: C. acnes is a major orthopaedic implant-associated infection (IAI) pathogen. Blood culture (BC) systems are increasingly used for culture of IAI specimens. Inconsistent and slow detection of C. acnes by different BC systems was detected. BACTEC Lytic/10 Anaerobic/F and BacT/ALERT SN detected C. acnes within 14 days. Thioglycolate broth and Schaedler agar proved a more reliable and faster option.